Battery Electric Vehicle with a Fuel Cell Stack - Wang, Shaohang; Xu, Yiwen (My University, 2019)
In this thesis project, a complete fuel cell system submodel, including a fuel cell stack, supplying system, and water management system was modelled. One Fuel Cell Plug-in Hybrid Electric Vehicle (FC-PHEV) and one Fuel Cell Hybrid Electric Vehicle (FC-HEV) model, as well as different components and control strategies, were also implemented in the GT-Suite software to simulate the hydrogen consumption under various driving cycles and scenarios. Furthermore, a cost analysis model is also developed to determine the optimal battery size for the FC-PHEV. Finally, a cost comparison among FC-PHEV, FC-HEV, and Battery Electric Vehicle (BEV)was made based on current data available from the U.S market. The Fuel Cell-PHEV model and the Fuel Cell-HEV model are validated against the WLTC and NEDC driving cycles. The functionality of the main control units is also evaluated. The simulation results show that: For the Fuel Cell-PHEV, the combined hydrogen consumption is 0.29 kg/100 km for NEDC, and 0.34 kg/100 km for WLTC. For the Fuel Cell-HEV, the hydrogen consumption is 0.68 kg/100 km for NEDC, and 0.82 kg/100 km for WLTC. The results of the initial cost comparison of energy source, based on current data show the ranking from the cheapest to the most expensive is FC-HEV, FC-PHEV, and BEV. The ranking of the total cost of ownership, including running cost from the cheapest to the most expensive is FC-PHEV, BEV, and FC-HEV. Overall, the Fuel Cell Plug-in Hybrid Electric Vehicle could be the best choice based on the current data.
Keywords: Energi; Transport; Hållbar utveckling; Elektroteknik; Energy; Transport; Sustainable Development; Electrical engineering